Prevalência de deficiência hipofisária na hemorragia subaracnóidea aneurismática - Gerival Vieira Junior (2016)
Introduction: Pituitary dysfunction is a condition that has been observed frequently in patients victims of aneurysmal subarachnoid haemorrhage (aSAH) and its prevalence has been little studied in the literature. Objective: The aim of this study was to determine the prevalence of hypopituitarism at the acute stage of aSAH as well as the chronic stage, at least 1 year after bleeding, to assess its correlation with clinical features of the studied population. Patients Methods: The prospective cohort study that evaluated patients admitted between June 2009 and October 2011 with a diagnosis of aSAH. Clinical and endocrine assessment was performed at the acute stage after hospital admission and before treatment at a mean of 7.5 (SD ± 3.8) days following aSAH. Another follow up was performed at a mean of 25.5 months (range: 12 55 months) after the bleeding. Results: A total of 92 patients were analyzed and 68 (73.9%) were followed in both acute and chronic phases. Dysfunction in the acute phase was lower among yonger compared to those without dysfunction (p < 0.05). The prevalence of dysfunction in the acute phase was higher among those with hydrocephalus on admission CT (57.9%) than among those without it (p < 0.05). At the chronic phase there was an association between pituitary dysfunction and Hunt & Hess scale > 2 (p < 0.05). Conclusions: There is not enough evidence to incorporate routine endocrinological evaluation to patients victims of SAH, but we should always keep this differential diagnosis in mind when conducting long-term assessments of this population.